# CDIM12 - CHAPTER 12 Coupled Oscillations 12-1 m1 = M k1 x1...

This preview shows pages 1–5. Sign up to view the full content.

CHAPTER 12 Coupled Oscillations 12-1. m 1 = M k 1 x 1 k 12 k 2 m 2 = M x 2 The equations of motion are ( ) () 11 1 2 1 1 2 2 22 1 2 2 1 2 1 0 0 Mx x x Mx x x κκ κ ++ = = ±± (1) We attempt a solution of the form it xt Be ω = = (2) Substitution of (2) into (1) yields ( ) ( ) 2 2 2 2 2 12 1 2 12 2 0 0 MB B BM B +− = −+ + = (3) In order for a non-trivial solution to exist, the determinant of coefficients of and must vanish. This yields 1 B 2 B ( ) ( ) 1 12 2 12 12 MM = 2   (4) from which we obtain 2 12 1 2 1 2 2 1 4 + (5) This result reduces to ( ) 2 12 12 M ωκ =+ ± for the case = = (compare Eq. (12.7)]. 397

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
398 CHAPTER 12 If were held fixed, the frequency of oscillation of m would be 2 m 1 ( 2 01 1 12 1 M ) ω κκ =+ (6) while in the reverse case, would oscillate with the frequency 2 m ( 2 02 2 12 1 M ) (7) Comparing (6) and (7) with the two frequencies, + and , given by (5), we find () 2 22 12 1 2 1 2 1 24 2 M κ +  + + +   ωκ 2 1 2 12 11 2 0 2 2 MM + + = + = 1 >+ (8) so that 01 + > (9) Similarly, 2 1 2 1 2 1 2 M + + 2 1 21 2 0 2 2 + = + = 2 <+ (10) so that 02 < (11) If , then the ordering of the frequencies is 1 > 2 01 02 ωω + >>> (12) 12-2. From the preceding problem we find that for 12 1 2 , ± 2 2 ; ++ ≅≅ (1) If we use 1 01 02 ; 2 == (2) then the frequencies in (1) can be expressed as
COUPLED OSCILLATIONS 399 () 12 10 1 0 1 1 1 12 20 2 0 2 2 2 11 κ ωω ω ε =+ ≅+ (3) where 12 12 12 ; 22 == (4) For the initial conditions [Eq. 12.22)], ( ) ( ) ( ) ( ) 1 212 0 , 00 x x x === ±± , = xD (5) the solution for ( ) 1 xt is just Eq. (12.24): 1 cos cos D t t +  =   (6) Using (3), we can write ( ) ( ) 1 2 01 02 1 01 2 02 ++ += + + + ≡Ω+ (7) ( ) ( ) 1 2 01 02 1 01 2 02 −− =−+ (8) Then, ( ) ( ) ( ) 1 cos cos xt D t t t t =Ω + + (9) Similarly, ( 2 sin sin sin sin t t Dt t t +− ) t = + + (10) Expanding the cosine and sine functions in (9) and (10) and taking account of the fact that + and are small quantities, we find, to first order in the ’s, ( ) 1 cos cos sin cos cos sin D t t t t t t t t + − ++ − −+ ≅ΩΩ −ΩΩ   (11) ( ) 2 sin sin cos sin sin cos D t t t t t t t t ++− + ΩΩ +ΩΩ (12) When either ( ) 1 or ( ) 2 reaches a maximum, the other is at a minimum which is greater than zero. Thus, the energy is never transferred completely to one of the oscillators.

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
400 CHAPTER 12 12-3. The equations of motion are 2 12 0 1 2 22 0 2 0 0 m xxx M m M ω ++= ±± (1) We try solutions of the form ( ) ( ) 11 ; it xt Be == (2) We require a non-trivial solution (i.e., the determinant of the coefficients of B and equal to zero), and obtain 1 2 B ( ) 2 2 4 0 0 m M ωω    = (3) so that 2 0 m M −= ± (4) and then 2 2 0 1 m M = ± (5) Therefore, the frequencies of the normal modes are 2 0 1 2 0 2 1 1 m M m M = + = (6) where 1 corresponds to the symmetric mode and 2 to the antisymmetric mode. By inspection, one can see that the normal coordinates for this problem are the same as those for the example of Section 12.2 [i.e., Eq. (12.11)].
This is the end of the preview. Sign up to access the rest of the document.

### Page1 / 38

CDIM12 - CHAPTER 12 Coupled Oscillations 12-1 m1 = M k1 x1...

This preview shows document pages 1 - 5. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online